Comparison of the metabolic responses to ingestion of hydrothermally processed high-amylopectin content maize, uncooked maize starch or dextrose in healthy individuals. Issue 7 (14th April 2014) - Bracken, Richard M.; Gray, Benjamin J.; Turner, Daniel
<x content-type="archive" xml:space="preserve">Abstract</x> Optimal carbohydrate ingestion strategies as nutritional therapy for glycogen storage diseases have not been fully realised, in part, due to difficulties in accessing patient cohorts, alongside limited details on metabolic effects and insight into working mechanisms. The present pilot study compared glycaemic and fuel oxidation responses following the ingestion of a hydrothermally processed maize starch (HPMS), an uncooked maize starch (UCMS) and maize-derived dextrose (DEX) at rest and during and after exercise in healthy individuals. A total of eight participants (seven males and one female; body mass (BM) 76·9 (sem 5·2) kg) visited the laboratory on three occasions. During each visit, the participants ingested 1 g/kg BM of HPMS (Glycosade™), UCMS (Argo™) or DEX as a 10 % solution. Blood samples were collected over a 2 h rest period and for 2 h after a 60 min treadmill run at 65 (sem 1) % VO2max. Mean values with their standard errors were analysed using repeated-measures ANOVA. Blood glucose concentrations under the HPMS condition were significantly elevated from resting values at 90 min (P= 0·02) after ingestion compared with those under the UCMS (60 min; P= 0·02) and DEX (30 min; P= 0·001) conditions. The rate of carbohydrate use during exercise after the ingestion of HPMS was 7–9 % lower compared with that after the ingestion of either DEX or UCMS (P< 0·05). The total amount of lipids oxidised during exercise was greater under the HPMS condition (26·2 (sem 2·8) g) compared with that oxidised under the UCMS (19·6 (sem 2·7) g; P= 0·04) or DEX (20·6 (sem 3·6) g; P= 0·07) condition. The results demonstrated a glycaemic advantage to the ingestion of HPMS over that of UCMS or DEX. Carbohydrate oxidation was reduced after the ingestion of HPMS compared with that after the ingestion of UCMS or DEX, with a corresponding higher rate of endogenous lipid use during exercise.